How to Survey Citizens’ Compliance with COVID-19 Public Health Measures: Evidence from Three Survey Experiments - Daoust, Jean-François; Nadeau, Richard; Dassonneville, Ruth; Lachapelle, Erick; Bélanger, Éric; Savoie, Justin; van der Linden, Clifton (Journal of experimental political science, 2021)
The extent to which citizens comply with newly enacted public health measures such as social distancing or lockdowns strongly affects the propagation of the virus and the number of deaths from COVID-19. It is however very difficult to identify non-compliance through survey research because claiming to follow the rules is socially desirable. Using three survey experiments, we examine the efficacy of different ‘face-saving’ questions that aim to reduce social desirability in the measurement of compliance with public health measures. Our treatments soften the social norm of compliance by way of a short preamble in combination with a guilty-free answer choice making it easier for respondents to admit non-compliance. We find that self-reported non-compliance increases by up to +11 percentage points when making use of a face-saving question. Considering the current context and the importance of measuring non-compliance, we argue that researchers around the world should adopt our most efficient face-saving question.